Kajian Bioetika Stem Cell - A Review - Nadya, Nadya; Ramadhani, Cut Sari; Pertiwi, Ayu; Zuryani, Risna; Afifah Nst, Fitri (Media Literasi Indonesia, 2026)
Advances in biomedical science such as stem cells offer great potential in the field of health, especially for regenerative therapy and the treatment of degenerative diseases. However, behind these benefits lie various ethical and moral issues related to the origin of the tissue used for stem cells. For example, embryonic stem cells used for therapy and research raise various issues from different perspectives, such as religion, law, society, and science. Through a systematic literature review focusing on stem cell research and therapy from an ethical perspective, using a qualitative descriptive approach, in-depth information was gathered related to the concepts, moral values, and bioethical controversies that have arisen in the development of stem cell science. This study discusses stem cells from various perspectives, such as law, religion, society, science, including regulatory provisions in Indonesia. This study also reviews the development of stem cell bioethics, which began with moral issues related to the sources of stem cells used, such as the use of human embryos, to the existence of more ethical alternative solutions such as induced pluripotent stem cells (iPSCs). The application of stem cell therapy and research must be carried out in accordance with bioethical principles and principles that respect human dignity, so that its application is carried out responsibly and humanely. Thus, stem cells can provide optimal benefits and welfare for humanity.